EXPLORING EFL TEACHERS' EXPERIENCES USING MEMORIZATION METHOD TO ENHANCE STUDENT'S ENGLISH VOCABULARY MASTERY - Puteri, Siti Azizah; Pratama, Hendi; Widhiyanto, Widhiyanto (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study looks at the firsthand experience of an English teacher at MAN Barito Selatan in Central Kalimantan who used a memorization method to help students learn more vocabulary. In this narrative inquiry research, I look at how she uses this method every day, including the problems she runs into, how she changes her strategy, and the effects she sees. Over a month, in-depth interviews and the teacher's reflective diary were used to gather data. The most important findings from the research show that the English teacher uses creative ways to make memorization activities less boring. At first, the students were hesitant, but they slowly gained confidence as they got positive feedback. The most significant problems were that the students in the class had different levels of skill and that there was insufficient time and teaching resources. The English teacher made it very clear that memorization is not the primary goal, but rather a way to help students practice speaking. This study shows how important it is for teachers to be